Answer:
Is there a picture you are missing? We cant answer without knowing what the answer choices are.
Step-by-step explanation:
Divide both sides by 1.5
1.5x = 3
x = 2
Check the equation by plugging in the 2.
1.5(2) = 3
3 = 3
Answer:
D
Step-by-step explanation:
Got it right on test
Answer:
9y(2x - 1)(x - 2y)(x + 2y)
Step-by-step explanation:
Given
18x³y - 9x²y - 72xy³ + 36y³ ← factor out 9y from each term
= 9y(2x³ - x² - 8xy² + 4y²)
Factor the first/second and third/fourth term in the parenthesis
= 9y( x²(2x - 1) - 4y²(2x - 1)) ← factor out (2x - 1) from each term
= 9y(2x - 1)(x² - 4y²)
x² - 4y² is a difference of squares and factors in general as
a² - b² = (a - b)(a + b), thus
x² - 4y²
= x² - (2y)² = (x - 2y)(x + 2y), hence
18x³y - 9x²y + 72xy³ + 36y³
= 9y(2x - 1)(x - 2y)(x + 2y) ← in factored form
Answer:
3
Step-by-step explanation:
12÷4=3
Hope this will help you!